Exploring the Personal, Relational and Communal Role of Religion in Diepsloot - Thornton, Brenton Stephen (University of the Witwatersrand, Johannesburg, 2023)
South Africa has a populace that perpetuates diversity in every demographic group. Although there are peaceful aspects to this diversity, there are also conflicts that have been shown historically and contemporaneously. Township communities in South Africa have experienced a particular development over time, due to aspects such as racial discrimination from Apartheid. Religion within this context was explored due to its diverse and consistent presence within South African township communities. Diepsloot is a township with particularly high levels of psychosocial struggles. To understand if religion adversely affects or alleviates these issues, this study examined the role and function of religion in this community. Religious experiences, roles, and the meaning of religion as a meaning making system were explored using a hermeneutic, phenomenological approach in the marginalised township community of Diepsloot. The specific analysis employed was Interpretative Qualitative Analysis (IPA). Data were collected using qualitative, semi-structured interviews with 12 participants. The core theoretical areas of this study that were discussed was attachment theory and social identity theory in the context of religion; while ecological systems theory was also applied but used as a contextual tool to understand and organise the themes for each structural, ecological level of the social environment of Diepsloot. Qualitative findings suggested that there were four main themes of this study; The Personal Relationship with Religion and God, Internal and Interpersonal Religious Conflict, Discrimination Based on Different Beliefs, and Diepsloot Factors Contributing to the Disconnected Community. Within these results and discussion of this paper, religion was shown as a factor that significantly impacts the perceptions, feelings, and behaviours towards the self on a personal level, and others on an interpersonal and communal level. Religion therefore has a significant part to play in social settings, and it is recommended that more studies exploring the phenomenon of religion be explored qualitatively to contribute further to the subjective understanding of the psychology of research within such contexts.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Psychology to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2023
Keywords: UCTD; Religion; Religious Experience; Psychology of Religion; Interpretative Phenomenological Analysis; SDG-16: Peace, justice and strong institutions